The political role of women in Islam (The mandate of the Covenant in the first Abbasid era, model 132 AH / 232 AH - 750 AD / 847 AD) (Journal of the College of Basic Education, 2022)
It is assumed that the mandate of the Covenant, covenants, and charters related to it would be sanctified, and that it should be respected by the caliphs and maintain its application in order for it to have its prestige and respect in the hearts of the public, but what happened in the Abbasid era in general and the first Abbasid era - which is the subject of our study - in particular, is the opposite. Absolutely, as some of the caliphs canceled these covenants and forced their owners to abdicate, following various methods of intimidation and intimidation with them, and the issue of contracting the mandate of the covenant or violating it was related to the personal whims of the caliphs, and the whims of the blocs surrounding them within the Abbasid court.